EFL LEARNERS’ PERCEPTIONS AND EXPERIENCES OF PROJECT-BASED LEARNING: MOTIVATION, ENGAGEMENT, AND CHALLENGES - Pasca Kalisa; Muhammad Zaki Pahrul Hadi; Issy Yuliasri (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
Project-Based Learning (PBL) is known as a student-centered approach that fosters active learning, cooperation and authentic use of language in English as a Foreign Language (EFL) class. This study explores EFL learners’ opinions and experiences of PBL, especially their motivation, engagement, attitudes, preferences, obstacles, and support needs. The design was an explanatory sequential mixed techniques design. Quantitative data were collected from 135 undergraduate EFL learners through a structured questionnaire, and qualitative data were obtained through open-ended questionnaire replies to give more in-depth insights into learners’ experiences. Descriptive statistics were used to evaluate quantitative data and qualitative responses were thematically analyzed. The results indicated that learners’ perceptions of PBL were typically good. The perception item that received the highest score was “PBL makes English learning more interesting” (M = 4.06, SD = 0.95) while the highest score for motivation and engagement was active participation during project activities (M = 3.98, SD = 0.92). Learners also indicated positive perceptions about PBL, with the statement “I participate more when project topics are interesting” having the highest mean score (M = 4.11, SD = 0.96). The most preferred characteristic of PBL was creative activities (82.2%), followed by technological integration (63.7%). The most important criteria driving participation were interesting themes for projects (85.9%) and the opportunity to develop new skills (74.1%). Learners experienced some drawbacks with these benefits including Unequal group involvement (74.1%), Communication problems with group members (65.9%) and concerns over unfair marks (56.3%). The most important sorts of assistance for teachers were feedback (84.4%) and clear guidance (83.0%). The study suggests that PBL offers significant collaborative and engaging English language learning experiences. However, its success depends on good group administration, open assessment processes and continued teacher assistance.